Popular Struggle and Democracy in Scandinavia 1700-Present (Palgrave Studies in European Political Sociology, 2018)
This book focuses on popular struggles in Denmark, Norway and Sweden from 1700-2015, and how popular struggle in the form of hunger riots, tax rebellions, petition drives, strikes, demonstrations, public meetings and social movements paved the way for the introduction and development of civil liberties and political rights. The author portrays social and political mass mobilization of ordinary people as vital to the construction of democracy, and an essential condition for the formation of the Scandinavian welfare states. Popular Struggle and Democracy in Scandinavia shows the transnational connections between Denmark, Norway and Sweden and between Scandinavia and the rest of Europe, and also contains a comparison of popular struggle in Scandinavia seen in a wider European perspective. The book will be of interest to social scientists, historians and students and researchers with an interest in popular struggles in Scandinavia.